Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Burnout Pada PT. Indaco Warna Dunia (Regional Sales Purwokerto) - Alif Fajri Husaeni; Adi Wiratno (Media Ekonomi, 2020)
The purpose of this research is to find out whether leadership and motivation styles affect the burnout of employees. From the theoretical exposure then it can be formulated hypothesized that there is a leadership style influence against burnout, and there is a motivation influence against burnout in employees. The population in this study is all employees at PT. Indaco Warna Dunia (Regional Sales Purwokerto). Sampling techniques used are purposive sampling. Research data uses primary data in the form of questionnaires using 50 respondents. The results of this study showed that the leadership style influenced the desire of burnout. The better the leadership style of a company then the lower the employee will be against the burnout. Motivation also has a negative influence on burnout.